BER analysis of hybrid carrier system based on WFRFT with carrier frequency offset. Issue 21 (1st October 2015) - Wang, Zhenduo; Mei, Lin; Wang, Xiaolu; Sha, Xuejun; Zhang, Naitong
Abstract : Carrier frequency offset (CFO) due to Doppler shift or misaligned frequency between the transmitter and the receiver has a serious impact on both orthogonal frequency division multiplexing (OFDM) and single carrier (SC) communication systems. Inter‐carrier interference coefficients of OFDM system produced by CFO have been proposed and applied in analysing exact bit error rate (BER) upon diverse channel models. In this Letter, interference of hybrid carrier communication system based on weighted‐type fractional Fourier transform impaired by CFO is investigated, which is a weighted form of multi‐carrier and SC schemes, and then exact BER expression of BPSK modulation HC system is derived and verified by simulations.